Identification of genetic polymorphisms in DNA repair xenoderma pigmentosum group D gene and its association with head and neck cancer susceptibility in rural Indian population: a hospital based case-control study from south-western Maharashtra, India - Datkhile, Kailas D.; Vhaval, Rohit D.; Patil, Madhavi N.; Khamkar, Tejasvi S.; Durgawale, Pratik P.; Chougule, Pandurang G.; Tata, Neville; Patankar, Ritwij; Gudur, Anand; Kakade, Satish V. (International Journal of Research in Medical Sciences, 2017)
Background: Smoking and alcohol related head and neck cancer is a major concern of health risk in developing countries, such as India. In this study, we aimed to determine the frequency of polymorphisms in DNA repair gene, xeroderma pigmentosum complementation group D (XPD) at codon (cd) 156, cd199, cd320, cd751 in patients of oral cancer from South-Western Maharashtra, India and to evaluate their association with oral cancer development. Methods: We used polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) to analyze XPD gene polymorphisms in 320 patients with oral cancer and in 400 age and sex matched disease-free controls. Results: There was no significant difference in the genotype distribution between oral cancer patients and controls for each polymorphism (p>0.05) except XPD199. The result from our study showed that allele frequencies of selected genes were not statistically different between the groups for XPD Arg156, XPD Asn320, XPD Gln751. XPDMet199 (OR=29.44; 95% CI= (18.47-46.92); p≤0.0001) genotypes significantly increased the risk of head and neck cancer. Conclusions: This study indicates that polymorphisms in cd199 of XPD gene could play a role in modifying genetic susceptibility of individual to head and neck cancer inMaharashtra patients. Thus, the case-control study suggest that selected DNA repair genes represent genetic determinants in oral carcinogenesis along with other risk factors in the rural Indian population.